Korelasi Antara Kadar Leptin Dengan Endotelin-1 Pada Individu Hipertensi Dengan Obesitas - Anna Ulfah Rahayoe; Hananto Andriantoro (The Indonesian Heart Association, 2007)
Background.Hypertension is frequently found in obesity, although the mechanisms for obesity related hypertension are still unclear. Several studies showed the role of endothelin-1 in the development of hypertension asso-ciated with obesity. More recent studies showed the possibility for the role of leptin in obesity related hypertension. In vitro study with human umbilical vein endothelial cells (HUVECs) showed correlation between leptin and endothelin-1. The aim of this study was to clarify the relation-ship between leptin, body mass index (BMI), blood pressure (BP) and plasma endothelin-1 in obese hypertensive subjects.Methods.A cross sectional study was performed at National Cardiovas-cular Centre, Harapan Kita Jakarta, which included 80 Indonesian men. The subjects were divided into lean hypertensive and obese hypertensive. The plasma immunoreactive ET-1 and leptin were determined by ELISA method.Results.ET-1 level and leptin level were significantly higher in obese hy-pertensive subjects compared with lean hypertensive subjects. There are significant correlation between endothelin level with BMI (r = 0.32; p < 0.005). There are also significant correlation between leptin level with BMI (r = 0.533; p <0.01), but there are no correlation between plasma leptin and endothelin-1 level in obese hypertensive men.Conclusions.Leptin and ET-1 level were significantly increase in obese hypertensive subjects compared with lean hypertensive subjects. There is no correlation between leptin and ET-1 level in obese hypertensive subjects.